Blindheit in Deutschland: Vergleich zwischen bekannten Daten und Vorhersagen - Rohrschneider, Klaus (Der Ophthalmologe, 2012)
AIM: There are no exact figures on the number of blind and visually impaired persons in Germany. The purpose of this study was to compare the development over the last years with earlier predictions and an outlook into the future. METHODS: Data from scientific publications as well as the Federal Statistical Office and from organizations for the blind on the frequency of blindness was compared to the forecast development of blindness. In addition the development of the frequency of age-related macular degeneration (ARMD) was taken into consideration. RESULTS: While the proportion of over 60-year-olds has steadily increased from 21% in 1993 to 25.9% in 2009, the ratio of blind people has risen from 8.9 per 10,000 inhabitants in 1993 to 10.6 per 10,000 inhabitants in 2003. However, up to 2009 decreased every year to 9.7 which is approximately the same as 1995, although ARMD has also become much more frequent as the main cause. Additionally there are considerable differences up to a factor two between the various studies on the number of blind people in different regions of Germany. DISCUSSION: At present there are approximately 150,000 blind and about 500,000 visually impaired persons in Germany. However, these numbers are only on the basis of estimates and according to studies in other European nations. Similar uncertainty exists concerning the diseases causing blindness. A transfer from epidemiological studies is limited especially because of the different definition of blindness. The expected increase of visually impaired and blind persons for the last 20 years as a result of the increasing age cannot be confirmed from the present data. It would be desirable to extensively register the specifications to prevalence and incidence of visual impairment and blindness including valid information on the corresponding cause to confirm the rising importance of visual impairment.
Gesehen am 09.04.2018